Symbols of a Perfect Chaos in Markus Zusak’s Bridge of Clay: Through Traumatic Past to Better Future - Oksana Bohovyk; Andrii Bezrukov (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
In literary texts, the representation of symbols as one of the most prevalent and essential components of the cultural continuum is not always explicit and therefore needs the development of approaches to the identification of implicit symbolic narratives in fictional discourse. One of the most representative contemporary novels in terms of ‘symbolicalness’ is considered the epic novel Bridge of Clay (2018) by Markus Zusak. This breath-taking story revolves around the ‘ramshackle tragedy’ of the Dunbar family and brims with energy and pathos. The tale of an existential riddle is told inside out and back to front, rendering confusion to the readers and encouraging them to decipher various symbols. That is why this article focuses on literal and metaphorical symbols to trace their meaning-making capabilities in creating a perfect chaos in the book. The novelty of the study lies in the explication of the symbol as a hermeneutic intratextual mechanism of meaning-making and identifying its artistic potential, as well as interpreting the symbol as a way of comprehending the semantic sphere of the text. Furthermore, Bridge of Clay is a profoundly heartfelt story of brotherhood that offers an alternative model of masculinity. It is Clay, the most determined of the Dunbar sons, who builds the bridge to transcend humanness. It is the bridge, the central symbol of the novel, which appears to be a link between the past and the future.